Design of asymmetric electrolytes for aqueous zinc batteries - Shengmei Chen; Chunyi Zhi (Communications Chemistry)
Abstract Aqueous Zn batteries are gaining increasing research attention in the energy storage area due to their intrinsic safety, potentially low cost and environmental friendliness; however, the zinc dendrite formation, zinc corrosion, passivation and the hydrogen evolution reaction induced by water at the anode side, and materials dissolution as well as intrinsic poor reaction kinetics at cathode side in aqueous systems, seriously shorten the cycling life and decrease energy density of batteries and greatly hinder their development. Recent advancements in asymmetric electrolytes with various functions are promising to overcome such challenges for zinc batteries at the same time. It has been proved that the applications of asymmetric electrolytes show significant contributions in the field of zinc-based batteries in suppressing side reactions while maintaining electrochemical performance to satisfy both anode and cathode. Therefore, this perspective summarizes recent advancements in asymmetric electrolytes’ design and applications for zinc batteries and outlines opportunities and future challenges, expecting continued research attention in this area.